FUNGSI KEPEMIMPINAN DALAM PERSPEKTIF ISLAM - Sola, Ermi (Department of Islamic Education Management, 2024)
A leader is a figure who is a unifier for anyone who is in his leadership area. In fact, the existence of a leader will always be accompanied by his expertise and readiness in recognizing, guiding, focusing and mobilizing the people under his responsibility to achieve common goals. Islamic leadership involves the role and activities of a leader who is able to influence other people based on Islamic rules contained in the Qur'an and Hadith. The concept of leadership in the Al-Qur'an is built on a strong and solid foundation. These foundations have been built for centuries and have become the guiding principles of Islamic education up to the present day. Islamic education requires leaders who with their leadership are able to influence group activities in an organized manner in an effort to achieve the goals of Islamic education. Leadership in the Islamic context without influence can result in people losing trust in their leaders. Next is the spiritual aspect; religious leaders, and the character inherent in leaders. Madrasah heads have an important responsibility, namely developing four basic competencies continuously for teachers to achieve educational and learning goals.